RNF168 Promotes Noncanonical K27 Ubiquitination to Signal DNA Damage - Gatti, Marco; Pinato, Sabrina; Maiolica, Alessio; Rocchio, Francesca; Prato, Maria Giulia; Aebersold, Ruedi; Penengo, Lorenza (Cell reports (Cambridge), 2015)
Ubiquitination regulates numerous cellular processes by generating a versatile communication system based on eight structurally and functionally different chains linked through distinct residues. Except for K48 and K63, the biological relevance of different linkages is largely unclear. Here, we show that RNF168 ubiquitin ligase promotes noncanonical K27-linked ubiquitination both in vivo and in vitro. We demonstrate that residue K27 of ubiquitin (UbK27) is required for RNF168-dependent chromatin ubiquitination, by targeting histones H2A/H2A.X, and that it is the major ubiquitin-based modification marking chromatin upon DNA damage. Indeed, UbK27 is strictly required for the proper activation of the DNA damage response (DDR) and is directly recognized by crucial DDR mediators, namely 53BP1, Rap80, RNF168, and RNF169. Mutation of UbK27 has dramatic consequences on DDR activation, preventing the recruitment of 53BP1 and BRCA1 to DDR foci. Similarly to the DDR, atypical ubiquitin chains could play unanticipated roles in other crucial ubiquitin-mediated biological processes. [Display omitted] •RNF168 mediates K27 ubiquitination of histone H2As•K27 ubiquitination is the major ubiquitin mark on chromatin upon DNA damage•K27 is strictly required for proper activation of the DNA damage response•53BP1, Rap80, RNF168, and RNF169 directly recognize the K27 linkage Gatti et al. demonstrate that cells respond to genotoxic stress by inducing K27 ubiquitination, a modification essential for activation of the DNA damage response and DNA repair. K27 ubiquitination is generated by RNF168 and targets the N-terminal tail of histone H2As.